STRATEGI PENGELOLAAN OBYEK WISATA NUSANTARA DI DESA PENIBUNG KABUPATEN PONTIANAK - Samuel Silalahi E.01106035 (FISIP Universitas Tanjungpura, 2013)
The tourism industry is growing rapidly today, had wonder if the tourism sector became prometteurs in increasing the level of a country's economy. Pontianak regency government especially the Department of Culture and Tourism as a Pontianak District Office which oversees tourism must work harder to manage object Tourism archipelago. Authors limit problem: How Internal And External Factors Management Strategy attractions archipelago in Pontianak Regency Village Penibung? In the management strategy, there are still many obstacles starting from lack of attention attraction by the government, particularly the lack of skilled human resources in tourism so that many facilities were damaged, lack of public awareness around the tourist sites and tourist response is still very minimal in object Tourism archipelago. As for the purpose of this research is How management strategy that has been applied to the archipelago Attraction, human factors, the role of communities around tourist sites, government policy, the level of visitor satisfaction. Here the authors use research methods research deskriktif types and data collection techniques used in this study is the observation, interviews, documentation. while the data analysis techniques the author uses descriptive qualitative technique in which data have been collected processed analyzedqualitatively. From the analysis of the data shows the object management strategy Tourism archipelago are still very minimal and less than optimal expected government policy in managing the attraction, improvement of human resources, the level of public awareness and attraction of tourists to the archipelago.Keywords: attraction, management strategy, government policy.